Efektivitas Ekstrak Sereh Wangi, Daun Mengkudu, dan Daun Pepaya terhadap Hama Kumbang Bubuk Jagung (Sitophilus zeamais) - Mutiawati, Sabilah; Azwana, Azwana (Jurnal Ilmiah Pertanian ( JIPERTA), 2026)
This study aims to determine the effectiveness of lemongrass (Cymbopogon nardus) extract, noni leaves (Morinda citrifolia), and papaya leaves (Carica papaya) in suppressing the population of maize weevil pests (Sitophilus zeamais) during maize seed storage. The research was conducted at the Organic Chemistry Laboratory of the University of North Sumatra using a Completely Randomized Design (CRD) with 10 treatments and 3 replications. The data were analyzed using ANOVA and further tested with the DMRT at 5%. The results showed that the treatments had a significant effect on the mortality of S. zeamais (p 0.05). The highest mortality (65%) was obtained from the treatment of 15 g noni leaves and 15 g lemongrass per 100 g of maize seeds, whereas the control was only 7.5%. This effectiveness is related to bioactive compounds such as saponins, flavonoids, and citronellal, which are toxic to insects. These results indicate the potential use of local plant extracts as environmentally friendly botanical pesticides for controlling storage pests and maintaining the quality of corn seeds.